Physical activity in patients with coronary heart disease: results from the EUROASPIRE V Survey. (25th November 2020) - Fras, Z; Jankowski, P; Jug, B; Gaita, D; Wood, D.A; De Bacquer, D; Kotseva, K
Abstract: Background: Physical inactivity is common in patients with coronary heart disease (CHD) and associated with an unfavorable prognosis. The study aim was to assess the physical activity levels as well as the intention to become physically active in patients with stable CHD with an additional focus on the association with their risk profile. Methods: Analyses are based on the cross-sectional EUROASPIRE V survey, conducted under the auspices of the ESC EURObservational Research Project in 2016–2017. The survey encompassed 8, 261 CHD patients, included in 27 countries, with a mean age of 62.4 years (±9.6, range 18 - 80 years), 25.8% of them were female. Physical activity level according to the overall patients' risk profile and their medical management was assessed, and the intention to become physically active in order to reduce their risk for recurrent events was investigated. Results: The physical activity status found in CHD patients included was far from satisfactory in general, since only 34.4% of those interviewed were regularly physically active (for more than 30 minutes duration on average 5 times a week). Nearly half (47.3%) of the patients reported they are performing more everyday physical activity in general after the index event; while only every fifth patient (21.4%) reported to follow the specific exercise advice from a health or exercise professional, every tenth (11.3%) attending the fitness club or leisure centre, and only 6.1% joining the community walking groups. Regular exercise to increase physical fitness (defined as planned physical activity performed 3–5 times per week for 20–60 minutes) was confirmed by 34.8%, while interestingly 40.4% of patients declared regular physical activity as part of the self-reported lifestyle change in order to lose their body weight. A better cardiovascular risk profile as well as receiving physical activity advice or weight loss advice was associated with better physical activity levels. Conclusions: Although an increase in the proportion of patients being adequately physical active after their index event, physical activity levels remain suboptimal in many CHD patients. There is an obvious need for improvement, with regards to both finding more effective ways of advice and encouraging our patients to increase the amount of their everyday exercise, as well regularly to monitor their lifestyle change. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): The survey was supported through research grants to the European Society of Cardiology from Amgen, Eli Lilly, Sanofi (Gold Sponsors), Pfizer (Silver Sponsor), and Ferrer and Novo Nordisk (Bronze Sponsors).